Increasing phenolic and aromatic compounds extraction and maximizing liking of lemon verbena (Aloysia triphylla) infusions through the optimization of steeping temperature and time. (December 2019) - Rocha, C; Coelho, M; Lima, RC; Campos, FM; Pintado, M; Cunha, LM
Herbal infusions are a new emerging trend among consumers, appearing in the market in many different forms. Due to intense competition, the commercial success of herbal infusions largely depends on flavour. The identification of the best combinations of steeping time and water temperature for the preparation of Aloysia triphylla infusions using a central composite design and response surface methodology was performed. The procedure aimed to maximize its antioxidant activity, phenolic and aromatic compounds, and consumers' liking of the infusions. The antioxidant activity and phenolic content were evaluated using the 2, 2′-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid radical cation) method and the Folin–Ciocalteu procedure. The analysis of aromatic compounds was performed based on the method of terpenic compounds. Sensory evaluation encompassed overall liking using a 9-point hedonic scale. Antioxidant activity and extraction of most phenolic compounds was higher for longer steeping times and higher temperatures, with some presenting a contrasting effect due to degradation at higher temperatures for longer steeping times. Results for terpenic compounds showed similar contrasting patterns. Based on the quadratic response surface, it was possible to predict the maximum overall liking for lemon verbena infusions prepared by brewing for 6 min at 96 ℃. Under such conditions, extraction of bioactive compounds was kept at a high level, close to the maximum attainable, while reducing the extraction of bitter compounds. These results are considered of great importance for the development of premium infusions from organic lemon verbena leaves.